2005
DOI: 10.1080/17450390500216894
|View full text |Cite
|
Sign up to set email alerts
|

Intraruminal infusion of n-butyric acid induces an increase of ruminal papillae size independent of IGF-1 system in castrated bulls

Abstract: The objective of this study was to explore morphological alterations of rumen papillae induced by n-butyric acid in relation to the insulin-like growth factor (IGF) system in adult castrated bulls. Three animals fitted with rumen cannula were fed twice daily at a low and high nutritional level (LL and HL), i.e., at 1.1 x maintenance (M) and 1.6 x M, respectively. Diets contained artificial dried grass and concentrate (74:26 and 52:48). Bulls received no (B0) or daily intraruminal infusions of 500 g n-butyric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
6
33
2
Order By: Relevance
“…The observed changes were most prominent in the AR and RV resulting in a marked 41% and 62% increase, respectively, in papillae surface in these rumen regions of h/c-fed sheep. A 57% to 95% elevation in rumen papillae size was also found in concentrate-fed sheep (Goodlad, 1981), goats (Shen et al, 2004) and bulls (Shen et al, 2005). Together with other factors, such as lower intraruminal pH values (Gaebel et al, 1987;Brossard et al, 2004) and increased blood flow (Dobson, 1984;Thorlacius, 1972), this strongly supported the passive absorption of non-dissociated SCFA by passive diffusion (Bugaut, 1987;Gaebel et al, 1987;Sehested et al, 2000).…”
Section: Morphology Of Ruminal Mucosamentioning
confidence: 48%
“…The observed changes were most prominent in the AR and RV resulting in a marked 41% and 62% increase, respectively, in papillae surface in these rumen regions of h/c-fed sheep. A 57% to 95% elevation in rumen papillae size was also found in concentrate-fed sheep (Goodlad, 1981), goats (Shen et al, 2004) and bulls (Shen et al, 2005). Together with other factors, such as lower intraruminal pH values (Gaebel et al, 1987;Brossard et al, 2004) and increased blood flow (Dobson, 1984;Thorlacius, 1972), this strongly supported the passive absorption of non-dissociated SCFA by passive diffusion (Bugaut, 1987;Gaebel et al, 1987;Sehested et al, 2000).…”
Section: Morphology Of Ruminal Mucosamentioning
confidence: 48%
“…Exclusively, after 6 wk of concentrate diet, ARP3 has been found to be upregulated at translational level, as validated by Western blot. One can speculate that ARP3 is involved in the well-known studied diet-dependent morphological alterations of the ruminal epithelium (18,26,54,55). Supporting this hypothesis, recently, gene ontology analysis after comparison of gene expression profiles in ruminal tissue from cows fed with low-or high-concentrate diets revealed that the regulation of the actin cytoskeleton is one of the most effected pathways (58).…”
Section: Discussionmentioning
confidence: 70%
“…Sugar-beet molasses are known to elevate the proportion of butyric acid in the ruminal content of short-chain fatty acids (Shen et al, 2004). Results by Shen et al (2004) with goats, Shen et al (2005) with steers and Mentschel et al (2001) with calves, show that an increase of butyric acid content in the rumen, enhances the cell proliferation of the papillae, thus enhances the papillae length, shape and density. In the present study, we found no effect on the papillae shape or density of the papillae in atrium ruminis.…”
Section: Discussionmentioning
confidence: 92%